Technological Pedagogical Content Knowledge (TPACK) Concept of the Teacher Competence in English Teaching at Junior High School - Sa’adillah; Ira Iasha; Nor Izzatil Hasanah (ELITE Association Indonesia, 2023)
In this study, the researchers is interested in examine the teachers of junior high schools in Banjarmasin to find out how English teachers understanding of the TPACK concept and apply the TPACK concept in English teaching. The researchers used Mix method. The participants in this study are 5 teachers of English at Junior High schools in Banjarmasin. Data collection techniques used in this study were questionnaire, observation, and interviews. Meanwhile, in analyzing the data using data analysis, the researcher uses calculations in a Likert scale to calculate the results of the questionnaire. Also, from Miles and Huberman, namely data collection techniques, data reduction, data display, and conclusion drawing. The result of this study, teachers understanding of the Technological Pedagogical Content Knowledge (TPACK) shows positive result with percentage 79.8% (80%). It means teachers understanding of the (TPACK) concept at MTsN 3 Banjarmasin get “Good” grades. While in implementing, TPACK concept on English teacher’s competence are good at applying the TPACK concept, especially in the aspects of TK, CK, PK and PCK in the classroom, it is just that the facilities available in schools are limited so they cannot use technology in learning to the fullest. Keywords: Technological Pedagogical Content Knowledge, Teacher Competence, English Teaching